2020 Orange Book of Results - Volume 3 - United Nations Population Fund (United Nations, 2023)
The Orange Book of Results features a selection of country programme key results, including those that feed directly into the Strategic Plan 2018–2021 indicators and those that pertain specifically to a country programme and, hitherto, are reported only at the country level. With this publication, UNFPA has moved beyond “business as usual” by publishing annual results achieved in 2020 reported by country offices in the more than 150 countries where UNFPA supports reproductive health care for women, youth and adolescents.